STUDY ON THE CAPACITY UTILIZATION OF ORTHODOX BLACK TEA PRODUCTION LINE AT PT. PERKEBUNAN NUSANTARA VIII, PASIR NANGKA, CIANJUR - Sukardi dan Wahyu Gumilar (Jurnal Teknologi Industri Pertanian, 2010)
ABSTRACT  Capacity is a maximum amount that such a production process can produce in a given unit of time. In 2007, Pasir Nangka Factory of PT. Perkebunan Nusantara VIII produced 2,493 tonnes of black tea. The optimum performance of the factory with 12 operation hours per day and 303 working days per year is 3,454 tonnes of dry black tea. The difference between those performances indicates that the factory operates in suboptimum condition.  The purposes of this research were (1) to  analyze the capacity utilization level of the orthodox black tea factory, (2) to find the costs caused by the idle and non-productive capacities, and (3) to analyze the alternatives to improve capacity utilization level. Analysis of capacity model was done by comparing actual capacity with practical capacity. Overall factory utilization level was determined by the drying line.  The production level of the overall factory achieved 72.2% in which 69% in productive status.  Therefore, 3.2% of the capacity was idle and 27.8% was non-productive. The results show that the alternative to reduce the idle time could increase the production capacity of overall factory from 69% to 72.2%, whereas alternative to increase the sprout production to meet demand of bottleneck line could improve the utilization of the overall productive capacity to 90.8%.  Keywords: orthodox black tea, factory, capacity, capacity utilization